Congenital chloride diarrhea in a Turkish boy - Özen, Hasan; Tanrıöger, Nihal (The Turkish Journal of Pediatrics, 1996)
Congenital chloride diarrhea (CCD), first described in 1945, is a rare, autosomal-recessively inherited disease. It is characterized by chronic, watery diarrhea with a high fecal chloride concentration, hyponatremia, hypokalemia, and hypochloremic metabolic alkalosis. In this report, a 7.5-year-old boy with CCD diagnosed by high fecal chloride concentration is presented. Until now CCD had not been reported from Turkey, although consanguineous marriages are common.
Keywords: congenital chloride diarrhea; stool chloride